Optimalisasi Kinerja Keuangan Melalui Analisis Rasio pada Organisasi Nirlaba: Studi Kasus Yayasan Hati Gembira IndonesiaOptimalisasi Kinerja Keuangan Melalui Analisis Rasio pada Organisasi Nirlaba: Studi Kasus Yayasan Hati Gembira Indonesia - Aprilia, Alya; Moh. Bintang Hidayah; Renal Pradisti; Rifka Fadila; Erwinsyah; Nina Yusnita Yamin; Rudi Usman (Ikatan Da'i Indonesia, 2025)
This study aims to determine the optimization of financial performance of non-profit organizations through ratio analysis, using a case study of Yayasan Hati Gembira Indonesia. The data collection technique used secondary data in the form of the foundation's financial reports for the period 2021 to 2023. The data analysis technique in this study used a quantitative descriptive method with calculations of the Working Capital Ratio, Current Ratio, and BOPPO Ratio (Operating Expenses to Operating Income). The results show that the Working Capital Ratio in 2021 was 48.35%, indicating strong liquidity, then decreased in 2022 to 23.1%, and declined again in 2023 to 21.45%, indicating that the foundation's ability to meet short-term obligations was decreasing. The Current Ratio followed a similar pattern, namely 48.35 in 2021, falling to 23.10 in 2022, and 21.45 in 2023. The BOPPO ratio shows the most efficient performance in 2021 at 90%, where income is greater than expenses, while in 2022 it jumped to 108.91%, indicating less efficiency (expenses exceed income), and in 2023 it was 102.43%, showing that the recovery of efficiency has not been fully realized.